2007
DOI: 10.1510/icvts.2006.137265
|View full text |Cite
|
Sign up to set email alerts
|

Contrast ultrasound imaging: the best method to detect type II endoleak during endovascular aneurysm repair follow-up☆

Abstract: The Cadence Contrast Pulse Sequencing with echo contrast agent is an ultrasound technique that substantially improves the ultrasound diagnostic reliability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
28
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 10 publications
3
28
0
Order By: Relevance
“…Unfortunately, recent reports do not show any substantial mid-or long-term follow-up for patients who are treated using similar angiographic embolization techniques. [6][7][8]10 Even when used during initial EVAR 14 or with follow-up via innovative ultrasound techniques, 17,19 results are not available beyond 2 years. Hypertension is prevalent in our patient cohort and has been identified as a preoperative T2EL risk factor in the population treated with the Zenith graft (Cook Medical Inc, Bloomington, Ind).…”
Section: Discussionmentioning
confidence: 99%
“…Unfortunately, recent reports do not show any substantial mid-or long-term follow-up for patients who are treated using similar angiographic embolization techniques. [6][7][8]10 Even when used during initial EVAR 14 or with follow-up via innovative ultrasound techniques, 17,19 results are not available beyond 2 years. Hypertension is prevalent in our patient cohort and has been identified as a preoperative T2EL risk factor in the population treated with the Zenith graft (Cook Medical Inc, Bloomington, Ind).…”
Section: Discussionmentioning
confidence: 99%
“…These findings support previous studies evaluating aortic stent grafts by CEUS imaging vs CTA, where sensitivity for endoleak detection was 50% to 100%, with many false-positive results. [25][26][27][28][29] Napoli et al, 30 however, reported 10 men with aneurysm enlargement and no evidence of endoleak during color-coded DUS imaging or CTA in whom CEUS scans performed with SonoVue detected endoleaks confirmed by conventional angiography. The authors suggest that CTA failure may have resulted from shorter imaging duration than with CEUS imaging; other published data have also confirmed 14 that CEUS imaging seems to be more sensitive than CTA in diagnosing low-flow endoleaks.…”
Section: Discussionmentioning
confidence: 99%
“…11-13 Some studies have increased detection of type II endoleaks with ultrasound contrast. 20,21 Although contrast-enhanced CDU imaging may aid in decreasing missed type II endoleaks, it increases the amount of false-positive results, may be too sensitive, and increases the cost of the study, the time of the study, and the invasiveness of the study because patients require an intravenous catheter. Finally, these studies have been in small cohorts, and this experience has not been used more broadly to truly assess its efficacy.…”
Section: Discussionmentioning
confidence: 99%